Measurement and Evaluation of Electric Field Strength in Samsun City Center - Çetin Kurnaz; Begüm Korunur Engiz (International Journal of Applied Methods in Electronics and Computers, 2016)
There has been a substantial growth in the use of mobile communication services over the last few years. As a result of this increase in the number of base stations, and electromagnetic (EM) exposure levels have become inevitable. Considering the public debate about possible health hazards caused by electric field strength (E), in this study, evaluating the effect of establishment of 4G systems on existing E levels is aimed. For this purpose; the total 536 E measurements were conducted in Samsun before and after 1 April 2016. It is seen from the measurements that maximum E ( E max ) is 6.32 V/m while the maximum average E ( E avg ) is 3.26 V/m which are both below the limits that are determined by the International Commission on Non-Ionizing Radiation Protection (ICNIRP) and Information and Communication Technologies Authority of Turkey ( ICTA). The results demonstrate that the deployment of 4G yielded up to 52.3% increase in E max while 12.5% in E avg values. Furthermore in order to determine the main E sources band selective E measurements are conducted and analysed. Analyses demonstrate that 65.6% of total E is caused by UMTS2100, 22.3% is produced by GSM900, 4.8% by GSM1800, 1.3 % by LTE800, and 6% is generated by devices that use the remaining frequency bands.